HUBUNGAN DERAJAT DYSMENORRHEA DENGAN KONSISTENSI FECES PADA MAHASISWI KEDOKTERAN UNIVERSITAS UDAYANA - Driansha, Cindy Liora; Adiatmika, I Putu Gede; Dinata, I Made Krisna; Purnawati, Susy (Universitas Udayana, 2022)
Gastrointestinal symptoms such as fecal consistency change commonly found in menstrual women. Women who have dysmenorrhea are likely to experience it than women without dysmenorrhea. This study aims to identify relationship between dysmenorrhea intensity with fecal consistency change among medical students of Udayana University. The hypothesis of this study is there is relationship between dysmenorrhea intensity with fecal consistency change among medical students of Udayana University. This study used analytic cross-sectional design. Questionnaires given to all medical students of Udayana University consists of questions about respondents’ identity, exclusion criteria, dysmenorrhea intensity in last menstruation based on Verbal Multi-dimensional Scoring System, and fecal consistency category based on Bristol Stool Scale. A total of 389 questionnaires collected and selected to rule out ineligible data. Eligible data were analyzed using descriptive test and Fisher Exact Test. Respondents involved in this study were female students aged 18-25 years. A number of 22.6% of respondents did not experience dysmenorrhea, while 59.1% had grade 1 dysmenorrhea, 16.5% grade 2, and 1.7% grade 3. A number of 14.8% of respondents had abnormal hard fecal consistency, 84.3 % normal, and 0.9% abnormal soft. There was no significant relationship between dysmenorrhea intensity and fecal consistency with P value equals to 0.238. This can caused by various factors such as diet, physical activity, sleep quality, stress, and different defecation habits of each respondents. Based on the results, it is concluded that there is no significant relationship between the dysmenorrhea intensity and the fecal consistency among medical students at Udayana University.